Made in Medway. - Rowland, Steve, ....-; Donnelly, Bianca, ....- ([S.l.] : BPR, 2008)
Made in Medway is a Creative hub for artists and designers in Medway. An online gallery, directory, archive and resource centre for art and design, fashion, photography, sculpture and mixed media. You are looking at the most recent work submitted by artists and designers on our directory. Showcasing the new and exciting work coming out of the Creative Industries in Medway area.